2022
DOI: 10.3389/fpsyg.2022.928928
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Long Working Hours, Occupational Stress, and Well-Being on Depression Among Couriers in Zhejiang, China

Abstract: Objective:This study aimed to examine the association between long working hours, occupational stress, depression, and well-being, and to explore the intermediary effect of occupational stress and well-being between working hours and depression among couriers in Zhejiang, China.Methods:The study used a cluster random sampling method to select 1,200 couriers from mainstream express companies in Zhejiang, China. The data were collected and analyzed using the Core Occupational Stress Scale (COSS) to measure occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
(46 reference statements)
0
8
0
3
Order By: Relevance
“…46,47 Working long hours will directly increase the ICU nurses' possibility of coming into contact with sources of occupational stress. 48 Along with differences in scores of HSE management standards based on gender, education, years of experience, monthly income and marital status, these major findings suggest an opportunity for developing intervention plans that take into account interpersonal differences. In addition, the positive correlation between the HSE management standards indicates that improving the performance of one of the standards could lead to improvement of the others.…”
Section: Discussionmentioning
confidence: 98%
“…46,47 Working long hours will directly increase the ICU nurses' possibility of coming into contact with sources of occupational stress. 48 Along with differences in scores of HSE management standards based on gender, education, years of experience, monthly income and marital status, these major findings suggest an opportunity for developing intervention plans that take into account interpersonal differences. In addition, the positive correlation between the HSE management standards indicates that improving the performance of one of the standards could lead to improvement of the others.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a study confirmed that working hours are a strong predictor of job stress, well-being, and depression. Long working hours have a significant indirect effect on depression through work stress (Hong et al, 2022). These days, some countries are working on reducing working days and hours.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Factors such as working hours, income, and job cognition are all related to job satisfaction and have a significant impact on well-being. Hong et al [ 26 ] found that long working hours was associated with occupational stress, well-being, and depression. This paper thus proposes the following research hypothesis:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%